Design aspects of bioreactors for solid-state fermentation: A review - H.K.Q, Ali; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr. (Croatian Association of Chemical Engineers, 2011)
Link to publisher's homepage at http://www.hdki.hr/index_en.htm